2017
DOI: 10.1021/acs.orglett.7b02567
|View full text |Cite
|
Sign up to set email alerts
|

Co-Catalyzed C(sp3)–H Oxidative Coupling of Glycine and Peptide Derivatives

Abstract: Cobalt-catalyzed selective α-alkylation and α-heteroarylation processes of α-amino esters and peptide derivatives are described. These cross-dehydrogenative reactions occur under mild conditions and allow for the rapid assembly of structurally diverse α-amino carbonyl compounds. Unlike enolate chemistry, these methods are distinguished by their site-specificity, occur without racemization of the existing chiral centers, and exhibit total selectivity for aryl glycine motifs over other amino acid units, hence pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 54 publications
2
70
0
1
Order By: Relevance
“…More recently, the group of Correa reported an efficient Co-catalyzed C(sp 3 )-H oxidative coupling of N-aryl glycine and peptide derivatives 5 with indoles or cyclic ethers (Scheme 3). [14] The α-C-H bond at the N-terminus of protected glycines or di-and tripeptides was oxidized with TBHP in the presence of catalytic amounts of Co(acac) 2 at 60°C. The authors suggested a similar mechanism via an imine 11 as for the Cucatalyzed alkynylation or arylation reaction.…”
Section: N-aryl Glycine Derivativesmentioning
confidence: 99%
“…More recently, the group of Correa reported an efficient Co-catalyzed C(sp 3 )-H oxidative coupling of N-aryl glycine and peptide derivatives 5 with indoles or cyclic ethers (Scheme 3). [14] The α-C-H bond at the N-terminus of protected glycines or di-and tripeptides was oxidized with TBHP in the presence of catalytic amounts of Co(acac) 2 at 60°C. The authors suggested a similar mechanism via an imine 11 as for the Cucatalyzed alkynylation or arylation reaction.…”
Section: N-aryl Glycine Derivativesmentioning
confidence: 99%
“…Correa and co‐workers developed a method to functionalize glycine esters and short peptides with ethers and indoles (Scheme ) . In previous studies involving CDC coupling between glycine esters and ethers, a [4+2] cyclization was observed with iron catalysis, leading to quinoline‐fused lactones (vide supra) .…”
Section: Cdc Reactions Catalyzed By Cobaltmentioning
confidence: 99%
“…Correa and co-workers developed aC (sp 3 )ÀHf unctionalization strategy for glycine derivatives 152 by using cost-efficient cobalt catalysis (Scheme 44). [101] Under this strategy,e thers and indoles were selectively introduced into glycined erivatives under base-free, mild, and straightforwardc onditions that allowed full retention of the configurationo ft he existing stereocenters.M echanistically,i tw as suggested that the reaction may proceedt hrough ac atalytic cycle that involved Co II /Co III speciesa nd af ew radicala nd cation intermediates. Nucleophilic indolesw ere reactedw ith the intermediate to give the desired product, whereas less-reactive ethers could react with the in-situ-generated a-oxy radicalt oproduce the corresponding coupling product.…”
Section: Modification Of Amino Acids and Peptidesmentioning
confidence: 99%
“…Correa and co‐workers developed a C(sp 3 )−H functionalization strategy for glycine derivatives 152 by using cost‐efficient cobalt catalysis (Scheme ) . Under this strategy, ethers and indoles were selectively introduced into glycine derivatives under base‐free, mild, and straightforward conditions that allowed full retention of the configuration of the existing stereocenters.…”
Section: Modification Of Amino Acids and Peptidesmentioning
confidence: 99%